Meat markets : the cultural history of bloody London - Geier, Ted (Theodore) (Edinburgh University Press, 2017)
Meat Markets articulates the emergent ́⁰nonhuman thought́⁰₉ developed across literatures of the long nineteenth century and inflecting recent critical theories of abject life and animality. It presents important connections between meat and popular serial press industries, the intersections of criminals and public readership, and the long history of bloody spectacle at Londoń⁰₉s Smithfield Market including public executions, criminal escapades, death and horror tales, and the fungible ́⁰penny presś⁰₉ forms of mass consumption. Through analysis of subjection, address, and narration in canonical and penny literatures, this book reveals the mutual forces of concern and consumption that afflict objects of a weird cultural history of bloody London across the long nineteenth century. Players include butchers, Smithfield, Parliament, Dickens, Romantics, Sweeney Todd, cattle, and a strange, impossible London.